Challenges of Community Radio in The Digital Era - Deddy Satria M; Syifa Urrahmah (SAINTIS Publishing, 2025)
This study explores the multifaceted challenges faced by community radio stations in Indonesia as they navigate the digital era. Employing a qualitative-descriptive methodology, the research combines literature review, field observations, informal interviews, and online content analysis to provide a comprehensive understanding of the socio-technical and institutional dynamics affecting community radios. Findings reveal persistent inequalities in digital infrastructure and access, particularly between urban and rural areas, which hinder digital adoption and audience expansion. Institutional fragility, ambiguous regulatory frameworks, and governance constraints further limit sustainability and adaptability. Moreover, community radios confront tensions between their participatory communication ideals and the pressures imposed by digital platforms driven by algorithms and commercial metrics. Despite these obstacles, innovative hybrid broadcasting models integrating analog and digital technologies emerge as promising pathways for survival and relevance. However, the success of such models depends on capacity building, supportive policies, and collaborative networks. The study concludes that sustaining community radio’s democratic and cultural mission in the digital age requires harmonizing technological adaptation with reaffirmed participatory values and inclusive policy frameworks. Recommendations highlight the need for equitable infrastructure development, targeted digital literacy training, policy reform, and fostering innovation through multi-stakeholder partnerships.